COVID-19 Pandemic in Yemen - Mohammed Al-Subari, Saleh Musaed; Saleem, Mohammad; Khadka, Sitaram; Ahmed Mahmood, Nagd Mohammed; Ziad Alhouzani, Talal M.; Shrestha, Dhan Bahadur (Journal of Karnali Academy of Health Sciences, 2020)
COVID-19, a global pandemic, has threatened the whole world with its devastating nature. Though, initially it has affected the developed countries, the countries in low- and middle-income category also are not spared. Yemen is a country with low-income economy and has been in an ongoing civil war. The first case of COVID-19 was reported on 10th April 2020 and there have been a total of 1619 cases along with 447 total deaths as of 21st July 2020. The preventive measures such as lockdown, social distancing, and personal hygiene are practiced, however there is still lack of adequate resources for efficient healthcare facilities. No drugs and vaccines are approved to fully rely on for the treatment of COVID-19, therefore the concept of “do not take the virus and do not give the virus” with different approaches of preventive aspects through hand-washing, social distancing, wearing masks and gloves, and making people aware in mass utilizing audio-visual media are helpful. Aids from different agencies and collaborative efforts of all the stakeholders are in need for the containment of COVID-19 cases in Yemen. By strengthening and increasing healthcare set-ups and resources, preparation of management guidelines by the government and mobilizing such resources to different parts for awareness, adequate reverse transcription-polymerase chain reaction (RT-PCR) tests, contact tracing, and safe quarantine and isolation services are essential.